Part I observational study on a new mechanism for North Pacific Oscillation influencing the tropics - Zhao, Jiuwei; Sung, Mi-Kyung; Park, Jae-Heung; Luo, Jing-Jia; Kug, Jong-Seong (Nature Publishing Group, 2023)
The North Pacific Oscillation (NPO), a representative midlatitude atmospheric variability, plays an important role in the development of the El Ni？o-Southern Oscillation (ENSO). To explain this extratropical？tropical linkage, previous studies have focused on the atmospheric boundary layer processes coupled with the mixed-layer ocean. Different from the existing hypothesis, in this study, we propose a new mechanism to link the NPO to ENSO via upper-tropospheric teleconnections. Analyses of the wave activity flux show that wave energy associated with the NPO directly propagates from midlatitude to the tropics, modulating the tropical circulation. During the NPO event, this equatorward energy flux becomes pronounced after the NPO peak phase and persists for more than two weeks. As a result, when a positive NPO grows (here, north anticyclonic？south cyclonic circulation), upper-level easterly wind anomalies are situated along the equatorial Pacific. Accordingly, anomalous lower-level westerly winds simultaneously occur in the equatorial Pacific, contributing to the development of El Ni？o events. To demonstrate the wave energy propagation via the upper-level troposphere, a stationary wave model experiment was performed with an NPO-like barotropic vorticity forcing. The results show equatorward wave propagation consistent with the observation.